Determinan dan kebijaksanaan pengentasan kemiskikan di diy: analisis rumah tangga berdasarkan susenas 1992 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
Abstract This study is designed to explain the incidence of poverty among 2304 households in Yogyakarta Special Region, based on the Indonesian Social and Economic Survey (SUSENAS) 1992. The incidence of poverty is classified into three categories: 'poor', 'almost poor' and 'not poor', measured by the proportion of food expenditure of the total household expenditure. Personal and job characteristics of heads of households, as well as the location of households are examined to explain the poverty in both urban and rural areas, using mukinomial logic model. The results show that (1) the incidence of poverty in Yogyakarta is relatively high in rural areas